The Influence of Empowerment, Work Environment, and Reward on Employee Performance through Employee Engagement as an Intervening Variable - Wahyu Ningsih, Agustin Tri (Journal La Sociale, 2026)
This study aims to analyze the influence of empowerment, work environment, and rewards on employee performance with employee engagement as an intervening variable in PT Berkarya Putra Inovasi. The research method used was quantitative with the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. Data was collected through the distribution of questionnaires to 128 employee respondents. The results of the study showed that empowerment does not have a significant effect on employee performance, but it has a significant effect on employee engagement. Work environment and rewards have been proven to have a significant effect on employee engagement and employee performance. Furthermore, employee engagement has a significant influence on employee performance and can be an intervening variable that strengthens the influence of empowerment, work environment, and rewards on performance. The implications of the research show the importance of companies in strengthening empowerment strategies, creating a conducive work environment, and providing fair rewards